Investigation of the Relationship between Coping with Humor and Perceived Stress Levels of Faculty of Sport Sciences Students - Aydın Şentürk; Cosmin Damian; Betül Altınok; Onur Sarı (Selcuk University, 2023)
The aim of this study is to examine the relationship between university students' levels of coping with humor and their perceived stress levels. As a data collection tool in the research, the Coping Humor Scale (CHS)) and The Perceived Stress Scale (PSS) was used. The participants of the research are N=135 university students studying at Dumlupınar University Faculty of Sport Sciences. As a result of the reliability analyzes of the scales used, the Cronbach Alpha coefficient of the Coping with Humor Scale was calculated as.52 and the Cronbach Alpha coefficient of the Perceived Stress Scale was calculated as .77. Correlation analyses were performed in order to answer the research question "Is there a significant relationship between the levels of coping with humor and perceived stress levels of the students studying at the Faculty of Sport Sciences?" Pearson correlation coefficients were examined in order to determine whether there is a relationship between the students' total scores on the scale of coping with humor and the perceived stress scale. As a result of the research; there is a significant negative correlation between students' levels of coping with humor and their perceived stress levels, r= -0.196, p